Unfolding the relations between companies and technologies under the Big Data umbrella - Canito, J. (2018)
Big Data is dominating the landscape as data originated in many sources keeps piling up. Information Technology (IT) business companies are making tremendous efforts to keep the pace with this wave of innovative technologies. This study aims to identify how the different IT companies are aligned with emerging Big Data technologies. The approach consisted in analyzing 11,505 news published between 2013 and 2016 and aggregated through Google News. The companies were categorized according to their position in the 2017 Gartner Magic Quadrant for advanced analytics. A text mining and topic modeling procedure assisted in summarizing the main findings. Leaders dominated a large fraction of the published news. Challengers are making a significant effort in investing in predictive analytics, overlooking other technologies such as those related to data preparation and integration. The results helped to shed light on the emerging field of Big Data from a corporate perspective.